Dakwah Jama’ah Haji Nusantara dari Masa Ke Masa - Zainal Zainal (Universitas Islam Negeri Imam Bonjol Padang, 2012)
The process of Islamization of the archipelago involving many people, not apart among pilgrims. Ka'batullah pilgrimage to Mecca became the center located in the dynamic development of Islam in the archipelago. Indonesia is a productive area to send people to visit Mecca in order to perform the Hajj. Then the roles they return from Mecca into a double, as well as uswah in the community, it can also convey the message of Islam to the people. It is possible, because the opportunity pilgrims to Mecca, in addition to performing throughout the pilgrimage circuit, they also have the opportunity explore the science of religion through halaqah-halaqah available. You can bet they contribute to the spread of Islam, besides traders from Arabia (strong suspicion has performed Hajj,) is also important. Therefore pilgrims preaching diverse experience in the spread of Islam in the archipelago, both during prakolonialisme (The royal or imperial), Dutch and Japanese colonial period, independence (the Old Order, New Order), and contemporary